Immunomodulation Eliminates Inflammation in the Hippocampus in Experimental Autoimmune Encephalomyelitis, but Does Not Ameliorate Anxiety-Like Behavior - Kocovski, Pece; Tabassum-Sheikh, Nuzhat; Marinis, Stephanie; Dang, Phuc T.; Hale, Matthew W.; Orian, Jacqueline M. (Frontiers in Immunology, 2021)
Multiple sclerosis (MS) is an autoimmune disease targeting the central nervous system, characterized by an unpredictable disease course and a wide range of symptoms. Emotional and cognitive deficits are now recognized as primary disease manifestations and not simply the consequence of living with a chronic condition, raising questions regarding the efficacy of current therapeutics for these specific symptoms. Mechanisms underlying psychiatric sequelae in MS are believed to be similar to those underlying pathogenesis, that is mediated by cytokines and other inflammatory mediators. To gain insight into the pathogenesis of MS depression, we performed behavioral assays in the murine experimental autoimmune encephalomyelitis (EAE) MS model, in the presence or absence of immunomodulation using the drug FTY720, an analogue of the lipid signaling molecule sphingosine-1-phosphate (S1P). Specifically, mice were challenged with the elevated plus maze (EPM) test, a validated experimental paradigm for rodent-specific anxiety-like behaviour. FTY720 treatment failed to ameliorate anxiety-like symptoms, irrespective of dosage. On the other hand, it was effective in reducing inflammatory infiltration, microglial reactivity and levels of pro-inflammatory molecules in the hippocampus, confirming the anti-inflammatory capacity of treatment. To explore the absence of FTY720 effect on behaviour, we confirmed expression of S1P receptors (S1PR) S1PR1, S1PR3 and S1PR5 in the hippocampus and mapped the dynamics of these receptors in response to drug treatment alone, or in combination with EAE induction. We identified a complex pattern of responses, differing between (1) receptors, (2) dosage and (3) hippocampal sub-field. FTY720 treatment in the absence of EAE resulted in overall downregulation of S1PR1 and S1PR3, while S1PR5 exhibited a dose-dependent upregulation. EAE induction alone resulted in overall downregulation of all three receptors. On the other hand, combined FTY720 and EAE showed generally no effect on S1PR1 and S1PR3 expression except for the fimbrium region, but strong upregulation of S1PR5 over the range of doses examined. These data illustrate a hitherto undescribed complexity of S1PR response to FTY720 in the hippocampus, independent of drug effect on effector immune cells, but simultaneously emphasize the need to explore novel treatment strategies to specifically address mood disorders in MS.